HUBUNGAN MINAT BELAJAR DAN PEMANFAATAN BUKU TEKS DENGAN HASIL BELAJAR MATA PELAJARAN EKONOMI DI SMA - Chintya Eka Putri; Z Mawardi Effendi (Jurnal Ecogen, 2019)
Interest in learning and the use of textbooks are two aspects that are very influential and have a relationship with student learning outcomes. This can be seen in the learning activities in the XI IPS class of SMAN 1 Luhak Nan Duo on economic subjects, the low student learning outcomes are influenced by students' lack of interest in learning and the lack of use of textbooks by students themselves. The research conducted at the XI IPS class at SMAN 1 Luhak Nan Duo aims to determine the relationship between learning interest and the use of textbooks with learning outcomes. This type of research is quantitative research with correlational methods. The instrument used in this study was a research questionnaire. The population is 130 students with samples randomly selected for 100 students. From the results of the analysis it can be concluded that: (1) Interest in learning and the use of textbooks have a positive and significant relationship together with learning outcomes seen from the Sig. F change 0,000 <0,05. (2) There is a positive and significant relationship between interest in learning and learning outcomes seen from the value of Sig. 0,000 <0,05. (3) There is a positive and significant relationship between the use of textbooks and learning outcomes of economic subjects seen from the Sig. 0,000 <0,05.Keyword : Interest in learning, utilization of textbooks, learning outcomes